A review of the China-Himalayan members of the subfamily Euplocaminae (Insecta: Lepidoptera: Tineidae) - Huang, Guo-Hua; Hirowatari, Toshiya; Wang, Min (Zootaxa, 2010)
The China-Himalayan members of the subfamily Euplocaminae Börner, 1938 are reviewed; two genera are treated: Euplocamus Latreille, 1809 and Psecadioides Butler, 1881, the latter of which is newly transferred to Euplocaminae. Psecadioides includes five species, three of which are described herein: Psecadioides cuneus Huang, Hirowatari & Wang, sp. nov. (type locality: China, Hainan), P. owadai Huang, Hirowatari & Wang, sp. nov. (type locality: Laos, Sam Neua), and P. prominens Huang, Hirowatari & Wang, sp. nov. (type locality: China, Hainan). We present the first records of Euplocamus melanchrodes Meyrick and Psecadioides tanylopha (Meyrick), comb. nov., from China and Japan, respectively. Relationships among Euplocaminae and its allied subfamilies are discussed. Keys to the genera and species of Euplocaminae of the region are provided, along with a distributional map of all nominal species.